Size Control of LaNbON2 Particles for Enhanced Photocatalytic Water Oxidation Under Visible Light Irradiation. (13th January 2021) - Seo, Jeongsuk
Abstract : Perovskite‐type LaNbON2 has the longest wavelength onset of visible light absorption—up to approximately 740 nm—among (oxy)nitrides based on transition metals Ti, Ta, and Nb. Water oxidation using visible‐light‐responsive LaNbON2 is challenging because the synthesis of the oxynitride has rarely been studied. Herein, we report the synthesis of small LaNbON2 particles and their size effect on photocatalytic water oxidation under visible light illumination. The small scheelite‐type LaNbO4, prepared by a polymerized complex method, was transformed into less‐defective LaNbON2 during nitridation as compared with that nitrided from LaNbO4 via a solid‐state reaction method. The small LaNbON2 particles, capable of absorbing intense visible light 700 nm above, improved the O2 evolution during 5 h of water oxidation under 300 W Xe light irradiation (λ > 420 nm). This enhancement was attributed to the size reduction of LaNbON2 particles, leading to increased surface area and encouragement of mild nitridation. Abstract : In this study, the perovskite LaNbON2, capable of absorbing intensive visible light up to 700 nm and above, were synthesized from the small scheelite‐type LaNbO4 prepared by a polymerized complex method. The small LaNbON2 particles enhanced the photocatalytic water oxidation activity under 300 W Xe light irradiation (λ > 420 nm).